Range expansion of an endangered beetle: Alpine Longhorn Rosalia alpina (Coleoptera: Cerambycidae) spreads to the lowlands of Central Europe - Cizek, Lukas; Schlaghamerský, Jiří; Bořucký, Jan; Hauck, David; Helešic, Jan (Entomologica Fennica, 2009)
Rosalia alpina is an endangered and strictly protected icon of saproxylic biodiversity throughout its range. Despite its popularity, information on its habitats and host-plants is insufficient, which may compromise the adoption of suitable conservation strategies. R. alpina has been considered as montane and associated with beech in central Europe, whereas in southern Europe R. alpina has often been reported from lowlands and its host spectrum is broader. We present evidence of an elm-feeding population ofR. alpina occurring in a lowland (beechfree) forest in the Czech Republic. This plus other information available suggest, that R. alpina spreads into central European lowland forests along large rivers, and that spectra of hosts and habitats exploited by R. alpina in Central Europe are wider than generally thought. Alteration of its habitat preference has either occurred in Central European populations, or lowland-inhabiting populations from the South are spreading northwards, possibly due to climate change.